Answer:
x=-5, y=-2. (-5, -2).
Step-by-step explanation:
x-3y=1
-x+6y=-7
----------------
3y=-6
y=-6/3
y=-2
x-3(-2)=1
x+6=1
x=1-6
x=-5
Answer:
y = 100 - 8(n - 1)
Step-by-step explanation:
I. if n = 1 or 1st year = 100 - 8(1-1) is 100
if n = 2 or 2nd year = 100 - 8(2-1) is 92
if n = 3 or 3rd year = 100 -8(3-1) is 84
Hope it'll help.
Answer:
I'm not sure, but I'll try
Step-by-step explanation:
(Side)^2 = (Hypotenuse)^2 - (Side)^2
(Side)^2 = (9)^2 - ( √ 65 )^2
(Side)^2 = (81) - (65)
(Side)^2 = 16
Take root of answer
Side = √16
Side = 4
Answer = 4